KALIMAT NEGATIF DALAM BAHASA INGGRIS DAN BAHASA MONI: SUATU ANALISIS KONTRASTIF - Kobogau, Mira (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRAK The research entitled â€œNegative Sentence in English and Moni language: A Contrastive Analysisâ€, aims at identifying, describing and contrasting the use of negative sentences in English and Moni language. The author would like to find the form and meaning of negative sentence in English and Moni. The English data have been collected from several books, whereas the Moni language have been collected from interviewing of some informants. The collected data were classified according to their categories and analyzed descriptively based on the theorities of Quirk and Verhaar in terms of negative sentence structure and contrast the two languages by using the theory of Lado. The results of this study indicate that similarities and differences can be found in all kinds of negative sentences. English and Moni language have the same structure in term of negative sentences. Both languages are free of negative elements in the form of a single morpheme and free of negative elements in the interrogative sentence structure serves as a predicate. Â Keyword : negative sentence structure, English and Moni language contrastive analysis.